2007
DOI: 10.4315/0362-028x-70.4.860
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance of Campylobacter spp. Isolated from Chicken Meat, Pork, and Beef in Korea, from 2001 to 2006

Abstract: A total of 770 samples of retail raw meat were examined for the presence of Campylobacter spp. The samples were obtained randomly from 232 retail stores in Korea from September 2001 to April 2006. The highest contamination rates were observed in chicken meat (220 181.4%] of 270 samples), whereas the rates of contamination in pork and beef were extremely low (1.6 and 1.2%, respectively). The antibiotic-resistant patterns of the 317 Campylobacter isolates were examined by the agar dilution method. Resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 34 publications
4
31
3
5
Order By: Relevance
“…Similar to our result, Hong et al (2007) also reported that 93.4% of the Campylobacter spp. isolated from retail raw meats, including chicken meats in Korea, were MDR.…”
supporting
confidence: 92%
“…Similar to our result, Hong et al (2007) also reported that 93.4% of the Campylobacter spp. isolated from retail raw meats, including chicken meats in Korea, were MDR.…”
supporting
confidence: 92%
“…was not found from all the samples in this study. That was quite different result from other study which showed contamination rate of 81.4% in chicken meat, 1.6% pork and 1.2% beef (Hong et al, 2007). It could be explained obligatory application of HACCP to chicken slaughter house in 2003 and recent increase of HACCP application.…”
Section: Discussioncontrasting
confidence: 62%
“…isolates was found in chicken meat from Korea than in meat from other East Asian countries (4,24), with ciprofloxacin-nalidixic acid-tetracycline resistance being the most frequent resistance profile. Hong et al (24) reported that 93.4z of the Campylobacter spp. isolated from chicken meats in Korea showed this antibiotic resistance triad pattern.…”
mentioning
confidence: 91%